2021
DOI: 10.1111/ans.17354
|View full text |Cite
|
Sign up to set email alerts
|

Reduced presentations with fractures or orthopaedic infections to a major children's hospital during a national COVID‐19 elimination strategy

Abstract: Background From 26 March 2020, New Zealand implemented a COVID‐19 elimination strategy which initially involved substantive limitations on public movement and assembly, and closure of non‐essential businesses. We asked what effect this had on acute paediatric orthopaedic presentations to a tertiary children's hospital. Method The numbers, age and gender of patients with orthopaedic presentations, seen by either the Children's Emergency Department (CED) or the orthopaedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
2
6
0
Order By: Relevance
“…One of the most noticeable medium-term health benefits of the zero-COVID-19 strategy is the reduced presence of infectious diseases (e.g., [ 26 ]). In a study of Kawasaki disease, a communicable disease that can cause high fever and coronary vasculitis in children, researchers found that compared to 2018 and 2019, the incidence of the disease in Taiwan decreased by 30% and 31% in 2020, respectively [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most noticeable medium-term health benefits of the zero-COVID-19 strategy is the reduced presence of infectious diseases (e.g., [ 26 ]). In a study of Kawasaki disease, a communicable disease that can cause high fever and coronary vasculitis in children, researchers found that compared to 2018 and 2019, the incidence of the disease in Taiwan decreased by 30% and 31% in 2020, respectively [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, in light of the unintended consequences that the zero-COVID-19 strategy could cause, such as a high demand for health care professionals for testing and tracing, more rigorous empirical evidence is needed to reach a more grounded conclusion in terms of whether the strategy also has a positive impact on the physical and psychological health of health professionals and other vulnerable populations, including COVID and non-COVID patients. Other than potentially reduced knock-on effects on the overall health and social infrastructure, medium-term advantages of the zero-COVID-19 strategy, such as a reduced presence of other infectious diseases and relatively undisturbed economic productivity, have also been discussed in the literature [ 26 , 27 ]. In addition to the reduced presence of health conditions, such as fractures and Kawasaki disease [ 26 , 27 ], it is possible that the relatively low presence of monkeypox in zero-COVID-19 countries such as China may also be contributed to the zero-COVID-19 strategy’s rigorous capability in curbing the transmission of viruses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the New Zealand Government committed to an elimination strategy with a level four alert, declaring a state of national emergency on 25 March 2020. Level four was the most stringent and included the complete cessation of elective surgeries [ 79 ]. As a result, there was a 100% drop in elective surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…is may be because of increased hand hygiene and social distancing practiced to reduce COVID-19. 9,10 What organisms typically cause these infections? ABSSSIs in a generally healthy population are typically caused by Gram-positive pathogens, the most common being Staphylococcus aureus and beta-hemolytic streptococci.…”
Section: Instructions For Participation and Creditmentioning
confidence: 99%